Computational and experimental studies on copper-mediated selective cascade C–H/N–H annulation of electron-deficient acrylamide with arynes. Issue 6 (30th November 2018) - Chen, Chao; Hao, Yu; Zhang, Ting-Yu; Pan, Jin-Long; Ding, Jun; Xiang, Heng-Ye; Wang, Man; Ding, Tong-Mei; Duan, Abing; Zhang, Shu-Yu
Abstract : An efficient and convenient copper-mediated method has been developed to achieve direct cascade C–H/N–H annulation to synthesize 2-quinolinones from electron-deficient acrylamides and arynes. Abstract : An efficient and convenient copper-mediated method has been developed to achieve direct cascade C–H/N–H annulation to synthesize 2-quinolinones from electron-deficient acrylamides and arynes. This method highlights an emerging but simple strategy to transform inert C–H bonds into versatile functional groups in organic synthesis to provide a new method of synthesizing 2-quinolinones efficiently. Mechanistic investigations by experimental and density functional theory (DFT) studies suggest that an organometallic C–H activation via a Cu(iii ) intermediate is likely to be involved in the reaction.